Automatic Plants Watering System for Small Garden - Astutiningtyas, Maria Beata Inka; Nugraheni, Monika Margi; Suyoto, Suyoto (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Background: Automation is starting to dominate the world today. We are enter-ing a new era of computing technology, the Internet of Things (IoT), which is experiencing rapid development. IoT is a worldwide neural network in the cloud that connects a mixture of things, aiming to maximise the benefits of internet con-nectivity in transferring and processing data. Using IoT, one can monitor and control a device remotely with a computer or smartphone. IoT can apply in vari-ous fields, one of which is the smart garden. Objective: This research aims to design an automatic plant's watering system used to small gardens in houses. Smart Garden is an electronic control and garden monitoring system for the pro-cess of watering plants so that it can help people care for plants. Method: This paper presents a design of the Internet of Things for small gardens inside houses using Wireless networks and sensors.  In automatic watering plants, information about soil moisture needed for plants. Sensors are devices used for smart agricul-ture. Arduino Uno will control all system operations as monitoring the plant wa-tering system. Result: The result of this paper is a Plants Watering System De-sign for Small Garden at Homes.